Does the Use of Dictogloss Strategy Affect Writing Ability of Junior High School Students? - Nurjayanti Nurjayanti; Ahmad Jailani; Rini Fitria (INOVISH JOURNAL, 2022)
Writing ability becomes one of the difficulties encountered by students, moreover at the junior high school levels. One of the ways to solve this problem is by finding an appropriate way to teach this skill. This study aims to reveal the significant effect of using Dictogloss strategy on the students’ writing ability at Junior the High School levels. The study used a quasi-experimental design with pretest and posttest. The total population of the study was 160 eighth graders that consist of five classes. From the population, 64 students (two classes, one class as the experiment group, and the other as the control group) were taken as the samples through cluster random sampling. The data were obtained through tests, pretest and posttest. Then, they were analyzed using independent sample t-test and paired sample t-test. The result showed a significant effect of using Dictogloss strategy on the students’ writing ability with a = 0.05 > sig. 0.000. It indicates that Dictogloss strategy can be used to improve students’ writing ability at the Junior High School levels.